An Iterative Explicit Method for Parabolic Problems with Cylindrical Symmetry-Increased Accuracy on Non-Uniform Grid - Sahimi, Ahmad Salleh; Muda, Zaiton (1989)
In this paper, the alternating group explicit (AGt-j iterative method is applied to cylindrical problems involving regular domains on a non-uniform grid. The procedure uses the fractional splitting strategy which is applied alternately at each half (intermediate) time step on a tridiagonal system of difference equations. The method is shown to be more accurate than the corresponding AGE scheme solved earlier by the authors using an uniform grid system but with a reduced stability range.